The Oxford Handbook of the History of English 2012
DOI: 10.1093/oxfordhb/9780199922765.013.0030
|View full text |Cite
|
Sign up to set email alerts
|

Old news: Rethinking language change through Australian broadcast speech

Abstract: Like other forms of spoken language, broadcast speech changes over time. While longitudinal language shift is often difficult to pin down with any certainty, archival news recordings provide a valuable opportunity to gain access to our spoken past. The formal style and British-sounding accents of old news bulletins differ from the way Australian newsreaders speak today. This is due in part to the process of “decolonization,” when Australia developed its own identity, one that was independent of its British her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The voices heard in the Australian media provide a useful indication of the acceptability and connotations of various accents and speaking styles at different points in our history. For example, Price (2012) gives an overview of the changing language used in twentieth century Australian news broadcasts. She notes that for the first half of the century 'BBC English' was the clear broadcast standard and it was only in the late 1960s that more authentically Australian accents and varieties gained traction in news and current affairs reporting (Price 2012: 342Á344).…”
Section: Studies Of Attitudes To Accent and Varieties Of Australian Ementioning
confidence: 99%
“…The voices heard in the Australian media provide a useful indication of the acceptability and connotations of various accents and speaking styles at different points in our history. For example, Price (2012) gives an overview of the changing language used in twentieth century Australian news broadcasts. She notes that for the first half of the century 'BBC English' was the clear broadcast standard and it was only in the late 1960s that more authentically Australian accents and varieties gained traction in news and current affairs reporting (Price 2012: 342Á344).…”
Section: Studies Of Attitudes To Accent and Varieties Of Australian Ementioning
confidence: 99%
“…Supporting this view, Sussex (2004, p. 12) describes stereotypical AusE speakers as "laconic, self-deprecating individuals, usually male, rather taciturn but prone to intermittent bursts of humorous, creative language". However, despite the body of work on stereotypes surrounding broad AusE, other research focusing on "general" AusE has found it to have become more acceptable over time (Price 2012), particularly for status and solidarity, and power and competence (Bayard et al 2001;Bradley and Bradley 2001).…”
Section: Folklinguistic Understandings Of Broad and General Australia...mentioning
confidence: 99%
“…intermittent bursts of humorous, creative language". However, despite the body of work on stereotypes surrounding broad AusE, other research focusing on 'general' AusE has found it to have become more acceptable over time (Price 2012), particularly for status and solidarity, and power and competence (Bayard et al 2001;Bradley & Bradley 2001).…”
mentioning
confidence: 98%